Efficacy of the lumbar sympathetic ganglion block in lower limb pain and its application prospects during the perioperative period. Issue 4 (9th October 2022) - Zhang, Jing‐Han; Deng, Yan‐Ping; Geng, Min‐Jian
Abstract: The sympathetic nervous system is involved in the physiological pathogenesis of many different types of chronic pain. Sympathetic blocks can interrupt the reflex control system by intercepting the noxious afferent fibers accompanying autonomic nerves, resulting in changes in peripheral or central sensory processing. A lumbar sympathetic ganglion block (LSGB), as a treatment method, refers to the injection of nerve blockers into the corresponding lumbar sympathetic nerve segments, usually requiring imaging assistance (CT,  X‐ray, ultrasound) to guide. At present, LSGB has been widely used in the clinical treatment of lower limb pain, such as neuropathic pain, lower limb ischemic pain, and so on. Its mechanism of action may be through inhibiting sympathetic nerve activity and dilating blood vessels, thereby alleviating pain and inhibiting stress response. However, there are few reports of LSGB during the perioperative period, especially in postoperative pain and gastrointestinal function. Therefore, by studying the literature about LSGB‐related studies, this article reviews the anatomy of the lumbar sympathetic nerve (LSN), with its clinical application and possible mechanism. We reviewed the analgesic effect of LSGB in patients with lower limb pain and postoperative pain and the potential application prospects in the recovery of gastrointestinal function, finally providing a reference for its clinical application. Abstract : At present, a lumbar sympathetic ganglion block (LSGB) has been widely used in the clinical treatment of lower limb pain, such as neuropathic pain, lower limb ischemic pain, and so on. Its mechanism of action may be through inhibiting sympathetic nerve activity and dilating blood vessels, thereby alleviating pain and inhibiting stress response. However, there are few reports of LSGB during the perioperative period, especially in postoperative pain and gastrointestinal function. Therefore, through the literature retrieval about LSGB‐related studies,  this article reviews the anatomy of the lumbar sympathetic nerve, its clinical application, and possible mechanism, which elucidates the analgesic effect of LSGB in patients with lower limb pain and postoperative pain and the potential application prospects in the recovery of gastrointestinal function, finally providing a reference for its clinical application.